2010
DOI: 10.1074/jbc.m109.075952
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycosylation Is Essential for the Stability but Not the Signaling Function of the Interleukin-6 Signal Transducer Glycoprotein 130

Abstract: N-Linked glycosylation is an important determinant of protein structure and function. The interleukin-6 signal transducer glycoprotein 130 (gp130) is a common co-receptor for cytokines of the interleukin (IL)-6 family and is N-glycosylated at 9 of 11 potential sites. Whereas N-glycosylation of the extracellular domains D1-D3 of gp130 has been shown to be dispensable for binding of the gp130 ligand IL-6 and its cognate receptor in vitro, the role of the N-linked glycans on domains D4 and D6 is still unclear. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 39 publications
1
43
2
Order By: Relevance
“…While a corresponding increase in membranebound gp130 was noted in aging retina, levels of membrane-bound gp130 remained unchanged and actually trended toward decreased levels in DBA/2 mice. These discrepancies between mRNA and protein expression in response to glaucoma-specific stressors could be due to either translation or protein stability, which are both known to regulate gp130 protein levels [48][49][50]. Furthermore, these findings contrast with gp130 expression following acute injury in the retina, where protein expression of gp130 increases for up 48 hours after excitotoxic insult [51].…”
Section: Discussioncontrasting
confidence: 53%
“…While a corresponding increase in membranebound gp130 was noted in aging retina, levels of membrane-bound gp130 remained unchanged and actually trended toward decreased levels in DBA/2 mice. These discrepancies between mRNA and protein expression in response to glaucoma-specific stressors could be due to either translation or protein stability, which are both known to regulate gp130 protein levels [48][49][50]. Furthermore, these findings contrast with gp130 expression following acute injury in the retina, where protein expression of gp130 increases for up 48 hours after excitotoxic insult [51].…”
Section: Discussioncontrasting
confidence: 53%
“…Previous work on gp130 revealed that a variant where all nine functional N-glycosylation sites were mutated was predominantly degraded via the proteasome [24]. The small proportion that was transported to the cell surface was biologically active, however, letting the authors conclude that N-glycosylation of gp130 was important for the stability, but not for its signaling capacity [24].…”
Section: Introductionmentioning
confidence: 99%
“…The small proportion that was transported to the cell surface was biologically active, however, letting the authors conclude that N-glycosylation of gp130 was important for the stability, but not for its signaling capacity [24]. Furthermore, we have recently shown that N-glycosylation of the IL-6 receptor (IL-6R) is dispensable for its biological function, but rather influences limited proteolysis of the IL-6R by the metalloprotease ADAM17 [25].…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is secreted by Kupffer cells in the liver and acts through its receptor, IL-6R (CD126), on hepatocytes to elicit a variety of effects including mediating components of the APR, hepatic regeneration, and antiapoptotic and antinecrosis effects (Taub, 2004). The IL-6R can bind IL-6 as a soluble or as a membrane-bound protein (Rose-John et al, 2007) and the IL-6/IL-6R complex must bind two monomers of gp130 membrane protein to elicit signal transduction (Rose-John et al, 2007;Waetzig et al, 2010).…”
Section: Introductionmentioning
confidence: 99%